"Pop" Goes the National Debt - Dirk Mateer; Wayne Geerling; Stefani Milovanska-Farrington (Institute of Labor Economics (IZA), 2025)
This paper provides a novel way for instructors to teach about the perils of a large National Debt, which is currently 36 trillion. We provide a detailed lesson plan that utilizes balloons to illustrate the possible paths a society can take to address this issue. The lesson plan consists of an introduction, images and data that can be used to spur discussion and reflection, how to utilize the balloons to help students understand three different debt scenarios, and a series of follow-up questions and answers to help debrief the activity.
Keywords: A20; A21; 330; budget; debt; debt-to-GDP ratio; deficits; fiscal policy; national debt; revenue; spending